Influence of psychosocial factors at work on the non-departmental security officers of the National Guard of the Russian Federation - A. V. Korneeva; Ya. A. Korneeva (Acta Biomedica Scientifica)
An analysis of modern research has shown insufficient study of the labor factors that influence the development of various functional states of non-departmental security officers which allow to develop the recommendations to improve their psychological safety.   The aim of the study. To identify and to describe psychosocial factors at work in relation to the general functional state of the body, stress and performance of non-departmental security officers.   Methods. We used the General Nordic Questionnaire for Psychological and Social Factors at Work (QPSNordic), psychophysiological testing using “Psychophysiologist” device, M. Lüscher color preference test, multivariate statistical methods. The study involved 74 non-departmental security officers of the Arkhangelsk region.   Results. The general functional state of the body, stress and performance, measured by objective and projective methods, are differentially interconnected with psychosocial factors at work. The general functional state of the body is related with the personal attitude to the work performed; stress and performance – with factors of social support, organizational culture and work requirements. The general functional state of non-departmental security officers is favorably influenced by such factors as understanding the goals of the work performed and the expected results, satisfaction with the quality of work and labor safety. Insufficient ability to maintain good relations with the team unfavorably influences the general functional state of the officers. The factors of work intensity include one-type tasks, tight schedule, increased alertness during work and greater precision in movements. Risk factors are associated with strict working hours and insufficient attention of the manage-ment to the opinion and interests of subordinates. At the same time, the environmental resource is the possibility of realizing professional motives and demonstrating mastery in work, as well as a favorable organizational culture.